The Influence of Factors on Bitcoin Value Formation - Shirinyan Lada V.; Rohanova Hanna O.; Shirinyan Aram S. (Problemi Ekonomiki, 2018)
The study is based on hypotheses about the influence of factors on bitcoin value formation. The aim of the article is the scientific inquiry and determination of factors affecting bitcoin value with a high level of correlation. The list of factors includes 33 world indicators, among which there are other cryptocurrencies, fiat money, world indices of stock markets, shares of powerful global companies, prices for energy and precious metals. As a result of the study, independent influential factors are selected and a correlation-regression model of bitcoin value is built. The statistical significance of the factors included in the model and the correlation-regression equation that allows simulating bitcoin value is substantiated. Practical approval of the proposed model using the actual data of the identified influence factors is carried out. Prospects for further research in this direction are based on applying trends as to independent factors that markedly affect the value of a bitcoin in order to model its future value. In addition to the factors identified, a significant influence on bitcoin value can be made by supply and demand, bitcoin scalability, interference of government regulatory institutions, the shadow money market, volume and nature of news in the crypto currency market.